2012
DOI: 10.4103/0301-4738.100557
|View full text |Cite
|
Sign up to set email alerts
|

Causes, epidemiology, and long-term outcome of traumatic cataracts in children in rural India

Abstract: Purpose:To describe preoperative factors, long-term (>3 years) postoperative outcome and cost of traumatic cataracts in children in predominantly rural districts of western India.Subjects:Eighty-two traumatic cataracts in 81 children in a pediatric ophthalmology department of a tertiary eye-care center.Materials and Methods:Traumatic cataracts operated in 2004–2008 were reexamined prospectively in 2010–2011 using standardized technique. Cause and type of trauma, demographic factors, surgical intervention, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
36
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 13 publications
15
36
1
2
Order By: Relevance
“…[14] while Gogate P et al observed traumatic cataract in 48.8% of cases due to blunt trauma and 39% of cases due to sharp trauma. [15] In our study wooden material like stick, thorn was the major cause of traumatic cataract which matches closely with study of Memon MN et al [13] and Shah MA. [16] In our study, 67.5% had total cataract which matches with study of Panda A et al, which had 74% total cataract.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…[14] while Gogate P et al observed traumatic cataract in 48.8% of cases due to blunt trauma and 39% of cases due to sharp trauma. [15] In our study wooden material like stick, thorn was the major cause of traumatic cataract which matches closely with study of Memon MN et al [13] and Shah MA. [16] In our study, 67.5% had total cataract which matches with study of Panda A et al, which had 74% total cataract.…”
Section: Resultssupporting
confidence: 77%
“…[11] and Gogate P et al in 90.2% of patients. [15] Most common complications reported in our study were anterior chamber reaction and PCO, which is consistent with study of Memon MN et al [13] , Zaman M et al [9] , Synder et al [12] , Loncar VL et al [19] , Kumar S et al [17] Patients with uveitis were given topical corticosteroids (Prednisolone acetate 1% eye drops) and cycloplegics and they responded within six weeks. One (2.5%) patient with PCIOL in our study had intractable raised IOP; peripheral laser iridotomy was done and later on IOP remained normal.…”
Section: Initialsupporting
confidence: 81%
“…At the time of discharge with best correction, 43.4% subjects attained normal vision while 31.3% subjects had visual acuity 3/60 or less and 31.8% subjects had visual acuity less than 6/60 ( Gogate et al (2012) also found poor visual outcome in girls compared to boys 11 The visual outcome also appears to vary among various age groups in our study. We found that older children attained better In the study, visual outcome appears to be nonsignificantly better in the subjects who sustained …”
supporting
confidence: 49%
“…11 But a large study reporting traumatic cataracts from tribal regions of India had young adults with traumatic cataracts equally common in both the genders.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on traumatic paediatric cataract have been published from Asian countries such as India, (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Pakistan, (15,16) Nepal (17)(18)(19) and Korea. (20) However, a PubMed database search of published literature on traumatic paediatric cataracts from developing countries in the Southeast Asian region revealed that no such data is available.…”
Section: Introductionmentioning
confidence: 99%